The under‐ice microbiome of seasonally frozen lakes. (21st October 2013) - Bertilsson, Stefan; Burgin, Amy; Carey, Cayelan C.; Fey, Samuel B.; Grossart, Hans-Peter; Grubisic, Lorena M.; Jones, Ian D.; Kirillin, Georgiy; Lennon, Jay T.; Shade, Ashley; Smyth, Robyn L.
Abstract : Compared to the well‐studied open water of the "growing" season, under‐ice conditions in lakes are characterized by low and rather constant temperature, slow water movements, limited light availability, and reduced exchange with the surrounding landscape. These conditions interact with ice‐cover duration to shape microbial processes in temperate lakes and ultimately influence the phenology of community and ecosystem processes. We review the current knowledge on microorganisms in seasonally frozen lakes. Specifically, we highlight how under‐ice conditions alter lake physics and the ways that this can affect the distribution and metabolism of auto‐ and heterotrophic microorganisms. We identify functional traits that we hypothesize are important for understanding under‐ice dynamics and discuss how these traits influence species interactions. As ice coverage duration has already been seen to reduce as air temperatures have warmed, the dynamics of the under‐ice microbiome are important for understanding and predicting the dynamics and functioning of seasonally frozen lakes in the near future.